2012
DOI: 10.1002/jbmr.1684
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in hip fracture rates by race/ethnicity among older US adults

Abstract: Hip fracture incidence has declined among whites in the United States since 1995, but data on recent trends in racial and ethnic minorities are limited. The goal of this analysis was to investigate hip fracture incidence trends in racial/ethnic subgroups of older Medicare beneficiaries. We conducted a cohort study to determine annual hip fracture incidence rates from 2000 through 2009 using the Medicare national random 5% sample. Beneficiaries were eligible if they were !65 years of age and had 90 days of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 29 publications
13
98
2
Order By: Relevance
“…However, the fact that the sex differences in robustness only accounted for 52% of the differences in bone strength between women and men suggested that the difference in cortical tissue mineral density was not sufficient to mechanically offset both the lesser robustness and smaller cortical area of women compared with men. Despite the deficit in cortical area found for black women relative to black men in the current study, modern black women do not show a significantly greater risk of sustaining a fragility fracture compared with black men [3,5,33]. The reason for this discrepancy may suggest that sex differences in robustness and cortical area found in the femoral midshaft may not necessarily mean that this mass deficit also exists for fracture prone sites like the distal radius and proximal femur.…”
Section: Discussioncontrasting
confidence: 79%
“…However, the fact that the sex differences in robustness only accounted for 52% of the differences in bone strength between women and men suggested that the difference in cortical tissue mineral density was not sufficient to mechanically offset both the lesser robustness and smaller cortical area of women compared with men. Despite the deficit in cortical area found for black women relative to black men in the current study, modern black women do not show a significantly greater risk of sustaining a fragility fracture compared with black men [3,5,33]. The reason for this discrepancy may suggest that sex differences in robustness and cortical area found in the femoral midshaft may not necessarily mean that this mass deficit also exists for fracture prone sites like the distal radius and proximal femur.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, we have included data on secular trends in different ethnic groups in the United States. (15) Morin and colleagues (72) recently performed a brief update on the information presented by Cooper and colleagues, (5) and included some, but not all, of the countries we covered above, and did not cover the new studies in Asia. (60,(62)(63)(64)70) Our approach differs substantially from the two prior papers (5,72) in several aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in men, rates increased by 4.2% per year among Hispanics and remained almost the same in other ethnic groups. In a more recent cohort study examining hip fracture rates between 2000 and 2009, using a 5% random sample from the Medicare national database, Wright and colleagues (15) showed continued declines in hip fracture incidence in white women and men, whereas black and Asian beneficiaries experienced nonsignificant declines and the rates of Hispanic women and men changed minimally over time. As a result, ethnic minorities comprise an increasing proportion of hip fracture cases in the United States, with Hispanics increasing from 3% of cases in 1983 to 7% in 2000, and Asians from 2% in 1983 to 4% in 2000.…”
Section: North Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying patients at risk and treating osteoporosis before fracture has been a strategy with proven benefits. This has occurred in the absence of dedicated ''hip fracture centers'' [9,24]. Medical care and team-based approaches have improved with national patient safety measures.…”
Section: University Of Rochester Medical Centermentioning
confidence: 99%